Isolation of Probiotic Lactic Acid Bacteria (LAB) From Commercialized Yogurt Based on 16s rRNA Gene - Apriansyah Wibowo; Kaisar Akhmad Khan; Dewi Mustikaningtyas; Rizky Ajie Aprilianto (Sainteknol : Jurnal Sains dan Teknologi, 2025)
Yogurt, a globally cherished dairy product, is celebrated not only for its creamy texture and tangy flavour but also for its numerous health benefits, primarily attributed to lactic acid bacteria (LAB). Key LAB species such as Lactobacillus bulgaricus and Streptococcus thermophilus drive the fermentation process, transforming milk into yogurt through lactic acid production. This study aims to isolate and identify LAB species from various yogurt brands using the 16S rRNA gene, employing advanced microbial analysis techniques such as PCR. Yogurt samples from five different brands were collected from a local convenience store in Gunungpati, Central Java, Indonesia. The bacterial inoculation was carried out using MRS agar, and isolated colonies were subjected to direct colony PCR with primers 27f and 1492r. The PCR products were analyzed using agarose gel electrophoresis. The results demonstrated that direct colony PCR is an effective technique for rapidly and accurately detecting bacterial species without the need for DNA extraction. All five yogurt samples contained Lactobacillus sp., as evidenced by the amplification of DNA fragments approximately 1500 base pairs in size. This study confirms the specificity and effectiveness of the 27f/1492r primers in identifying Lactobacillus sp., providing more information for further research on the probiotic roles of LAB in yogurt quality and health impacts.